Pengaruh Kinerja Keuangan Terhadap Pertumbuhan Laba Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Siagian, Cristin Sasa Bela; Azhar, M. Karya Satya; Ika, Desi (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research aims to determine the effect of liquidity, leverage and profitability on profit growth with firm size as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2022. The sample research method used was purposive sampling. The total observations in this research were 228 companies consisting of 38 companies. The data analysis technique used in this research is Moderated Regression Analysis using the SPSS 26 analysis tool. The test results of this research show that liquidity, leverage, profitability and firm size simultaneously influence profit growth. Partially, liquidity proxied as Current Ratio and profitability proxied as Return On Assets have a positive effect on profit growth, while leverage proxied as Debt to Asset Ratio has no effect on profit growth. Firm size is able to moderate and strengthen the effect of the Debt to Asset Ratio and Return On Assets on profit growth, while firm size is not able to moderate and weaken the effect of the Current Ratio on profit growth.